LOGIKA FUZZY MENENTUKAN JUMLAH PRODUKSI BERDASARKAN PERSEDIAAN DAN JUMLAH PERMINTAAN - yenni, yusli (STKIP PGRI Sumatera Barat, 2017)
The complicated to determine total of product will be production with stock, make the process of decision be slowly. The purpose of this research for implementated fuzzy logic Mamdani method for determine the total of production basis on the total of stock and the total of request at OSI Electronics Batam, Corp and description of accuracy level. The first process analyze the corporation data with total 12 data start from January – December 2015. The data will be processed using MATLAB application with first step is fuzzyfication defene the membership function. There are 2 information as fuzzy input request and stock and will be processed using triangle and trapezoid membership function. Next step is implicated all rules and this research using 26 rules, rule compositions and the last step is defuzzyfication using bisector method. The accuracy using fuzzy logic that was built were 91,67% and error 9,37%.